Single Nucleotide Polymorphism of Genes Associated with Metabolic Fatty Liver Disease. (3rd February 2022) - Mu, Tong; Peng, Linrui; Xie, Xinglei; He, He; Shao, Qing; Wang, Xiran; Zhang, Yuwei
Abstract : Aims . The present study aimed to reveal the relationship between single nucleotide polymorphism (SNP) of PNPLA3, TM6SF2, MBOAT7, GATAD2A, and STAT3 genes and metabolism-related fatty liver disease (MAFLD), so as to provide a research basis for further exploring the diagnosis and treatment of diseases at the molecular level. Methods . A total of 564 patients were included in the physical examination center of Xinjiang Karamay People's Hospital. They were divided into an MAFLD case group and a healthy control group. The whole blood DNA of each sample was extracted by a whole blood genomic DNA extraction kit, and the genotypes of PNPLA3 rs738409, MBOAT7 rs64173, STAT3 rs744166, TM6SF2 rs58542926, and GATAD2A rs4808199 were performed; after adjusting for confounding factors, the additive model, dominant model, and recessive model of each gene were analyzed by multivariate logistic regression. Results . The CC genotype of the PNPLA3 gene rs738409 and the TT genotype of the MBOAT7 gene rs64173 are risk factors in the occurrence of MAFLD. The AA genotype of the STAT3 gene rs744166 is a protective factor of MAFLD, while TM6SF2 rs58542926 and GATAD2A rs4808199 show no significant correlation with MAFLD.